A Morphologycal Analysis Of Derivational Suffixes In Short Stories - Wulandari, Ayu; , Drs. Sigit Haryanto, M.Hum; , Dr. Dwi Haryanti, M.Hum (2014)
This research studies the derivational suffixes in short stories. The objectives of this study are to describe the form of derivational suffixes and to describe the function of derivational suffixes in short stories. This research is a descriptive qualitative research. The data are words taken from short stories. The data are collected by reading the short stories, giving an underline to the words which contain English derivational suffixes, classifying and writing the English noun of derivational suffixes. The techniques of collecting data is documentation, the steps are as follows identifying, classifying and drawing conclusion. The results of the study show that firstly from the whole data 205 there are the researcher finds four forms of derivational suffixes, the first is noun 47 data that consist -ance 4 data or 1,95%, -ence 1 datum or 0,48%, -ation 5 data or 2,43%, -ment 7 data or 3,41%, -ion 10 data or 4,87%, -ness 15 data or 7,31%, and -ity 1 datum or 0,48%. Second is verb 1 datum that consists -ize 1 datum or 0,48%. Third is adjective 38 data that consist -able 5 data or 2,43%, -ful 9 data or 4,39%, -less 12 data or 5,85%, -al 4 data or 1,95%, and -ous 6 data or 2,92%). Fourth is adverb 119 that consist -ly 119 data or 58,04%. Secondly, From the 205 data collected are the first suffixes from verb into noun 30 data that consist -ance 5 data or 2,43%, -ence 1 datum or 0,48%, -ation 5 data or 2,43%, -ment 8 data or 3,90%, -ion 11 data or 5,36%. The second is adjective into noun 17 data that consist -ion 1 datum or 0,48%, -ness 15 data or 7,31%, and ity 1 datum or 0,48%. The third is noun into verb 1 datum that consists 1 datum or 0,48%. The fourth is noun into adjective that consists -ous 4 data or 1,95%, -ful 5 data or 2,43%, -less 10 data or 4,87%, -able 2 data or 0,97%, and -al 2 data or 0,97%. The fifth is verb into adjective that consist -able 4 data or 1,95%, -ful 4 data or 1,95%, -al 2 data or 0,97, -ous 1 or 0,48%, and -less 2 data or 0,97%. The sixth is noun into adverb (- ly) 8 data or 3,90. The seventh is verb into adverb (-ly) 10 data or 4,87%. The eighth is adjective into adverb (-ly) 101 or 49,26%.